Public dentist in Finnmark : work conditions and challenges - Klaudiussen, Ida Johanne; Niskanen Hansen, Nina Marleena (Universitetet i Tromsø, 2012)
You can often hear people within the dental care system in Norway expressing that: “if you take a job in Finnmark you will get to do a lot and gain a lot of experience”. This claim might be based on the fact that there are very few specialists in Finnmark. In addition, low population density with long distances to dental service creates a high degree of independence and self-reliance among dental health personnel in the area. This combined with higher frequency of irregular treatment habits among adults and inferior oral health conditions compared to the rest of the country (St.meld 35) might yield an extra challenge to dentists, particularly in more remote areas of Finnmark.